The Role of the Teacher in Improving the Social Interaction of Children with Special Needs at the Gunungsitoli State Special School - Amstrong Harefa; Hendrikus Otniel Nasozaro Harefa (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine the role of teachers in increasing the social interaction of children with special needs in SLB Negeri Gunungsitoli. This study uses a qualitative method with a descriptive approach. The technique of determining the research subject is by using a purposive sampling technique. The research informants comprised 2 people, namely the Principal of the Gunungsitoli State SLB and 1 Gunungsitoli State SLB teacher. Data collection techniques with observation, interviews, and documentation. Data analysis techniques used in this study are data collection, data reduction, data presentation, and data verification and confirmation of conclusions. This study uses the triangulation method to obtain a technique for measuring the validity of the data. It was concluded that the Gunungsitoli State Special School (SLB) presence was very meaningful, especially for Children with Special Needs (ABK), especially regarding social interaction with peers in their learning environment and the community. Teachers must carry out persuasive strategies, and spiritual and humanist approaches, both between teachers and students and between students. Social interaction between students can be well established, active communication is established, and the creation of a spiritual relationship that continues to grow and develop.